PEMBELAJARAN SENI LUKIS ANAK MELALUI PENERAPAN TEORI KONSTRUKTIVISTIK - Edy Tri Sulistyo (Universitas Sebelas Maret, 2008)
The objective of this research was to find out the result of the learning process of how to paint using Constructivists theory. The classroom action research methodology was employed in this research. The sources of the data were place events and the children’s paintings. The techniques of data collection were participant observation and document analysis. The research result shows that the learning process using constructivists theory can increase children's creativity, the applying of the facilities influences the learning. Result the use of multimedia increase the children creativity, the holistic system of evaluation.